Molecular dynamics folding simulation of β-hairpins from protein G - Fatahiya, Mohamed Tap; Ameera, Ishak; Ragheed, Hussam; Nurul Bahiyah, Ahmad Khairudin (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/